Insights into Machining Techniques for Additively Manufactured Ti6Al4V Alloy: A Comprehensive Review - Abdulkadir Mohammed Sambo; Muhammad Younas; James Njuguna (Applied Sciences)
Investigation into the post-processing machinability of Ti6Al4V alloy is increasingly crucial in the manufacturing industry, particularly in the machining of additively manufactured (AM) Ti6Al4V alloy to ensure effective machining parameters. This review article summarizes various AM techniques and machining processes for Ti6Al4V alloy. It focuses on powder-based fusion AM techniques such as electron beam melting (EBM), selected laser melting (SLM), and direct metal deposition (DMD). The review addresses key aspects of machining Ti6Al4V alloy, including machining parameters, residual stress effects, hardness, microstructural changes, and surface defects introduced during the additive manufacturing (AM) process. Additionally, it covers the qualification process for machined components and the optimization of cutting parameters. It also examines the application of finite element analysis (FEA) in post-processing methods for Ti6Al4V alloy. The review reveals a scarcity of articles addressing the significance of post-processing methods and the qualification process for machined parts of Ti6Al4V alloy fabricated using such AM techniques. Consequently, this article focuses on the AM-based techniques for Ti6Al4V alloy parts to evaluate and understand the performance of the Johnson–Cook (J–C) model in predicting flow stress and cutting forces during machining of the alloy.